Delivering SMS-based mobile services using SOA - DURAN, Randall E. (Institutional Knowledge at Singapore Management University, 2012)
Over the past several years, mobile communications and architectures that support them have come into the mainstream for enabling businesses to communicate better with their customers. This chapter presents a mobile services design based on service oriented architecture (SOA) principles that was successfully used to implement mobile banking. The engineering methods used to design and deliver SMS-based mobile services using SOA are reviewed, and some of the practical challenges that were encountered with the implementation are explored. The capacity for this solution design to support native, thick-client mobile applications is also examined.